Analisis Keefektifan Kalimat dalam Sintaksis pada Teks Berita Daring Antaranews.com Edisi Januari 2024 sebagai Sumber Referensi bagi Siswa SMA Kelas XII - Yulita Ariani Fahrunnissa; Alayanna Isar Paramitha; Deasy Antoneta Purba; Natasya Intan Maharani; Wilda Robiatul Mahbubah; Asep Purwo Yudi Utomo; Bagas Kurnianto (STIKes Ibnu Sina Ajibarang, 2024)
This research analyzes the effectiveness of sentences in syntax in the January 2024 edition of Antaranews.com online news text as a reference source for XII grade high school students. This research aims To assess the efficacy of sentences in five articles published in online news, namely Antaranews.com, which is reviewed from the sentence structure, cohesion and coherence as well as the appropriateness of language styles. The methodological approach and theoretical approach are applied as approaches to the analysis of this research. The methodological approach uses a qualitative descriptive method, and the theoretical approach in Examining the efficacy of writing uses analytical methods in the field of syntax. In this analysis, the qualitative descriptive method is used, which is focused on the problem based on facts conducted by observation and studying existing documents and articles. The results of the analysis contained in 5 Antaranews.com news texts include 28 ineffective sentence structures, 23 ineffective cohesion and coherence, and also 11 stylistic discrepancies. This resulted in 62 ineffective sentences. This research is expected to contribute to the knowledge and insight of researchers about sentence analysis conducted in the context of online news texts. The most errors in the use of effective sentences are in sentence structure. Therefore, improvement efforts are needed to minimize and overcome sentence usage errors, to create good language in written communication. The practical implication of this research is the importance of a good understanding of sentence syntax in the context of language learning, especially for XII-grade high school students who need a deep understanding of building effective and clear news texts.